2016
DOI: 10.1016/j.coi.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of innate and adaptive immunity in metal-induced hypersensitivity

Abstract: Metal-induced hypersensitivity is driven by T cell sensitization to metal ions. Recent advances in our understanding of the complex interactions between innate and adaptive immunity have expanded our knowledge of the pathogenesis of these diseases. Metals activate the innate immune system through direct binding to pathogen recognition receptors, activation of the inflammasome, or the induction of cellular death and release of alarmins. Certain metals can serve as adjuvants, promoting dendritic cell activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
2
37
0
3
Order By: Relevance
“…Other insoluble metal salts such as beryllium hydroxide, have adjuvant properties that enhance sensitization and disease after pulmonary exposure [55]. Beryllium hydroxide induces release of caspase-1-independent IL-1α from necrotic alveolar macrophages and mediates its adjuvant effects on Th1 cells via MyD88-dependent receptors that enhance DC migration and function [56].…”
Section: Insoluble Salts and Other Particulate Adjuvantsmentioning
confidence: 99%
“…Other insoluble metal salts such as beryllium hydroxide, have adjuvant properties that enhance sensitization and disease after pulmonary exposure [55]. Beryllium hydroxide induces release of caspase-1-independent IL-1α from necrotic alveolar macrophages and mediates its adjuvant effects on Th1 cells via MyD88-dependent receptors that enhance DC migration and function [56].…”
Section: Insoluble Salts and Other Particulate Adjuvantsmentioning
confidence: 99%
“…Homeostasis of the human body can be maintained with proper control of the immune response. In addition, an abnormal or overactive immune system can cause pathogenic conditions, such as asthma, autoimmunity and hypersensitivity [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment of Be-exposed mice with neutralizing anti-TNF-α antibodies impairs IL-1α-dependent recruitment of neutrophils into the airways and mobilization of immunogenic pulmonary cDCs from the lung to the LDLNs. Neutrophil recruitment in Be-exposed mice is driven by IL-1α in Be-exposed mice with no evidence of a role for caspase-1, NALP3, or IL-1β (2,36). Therefore, we predicted that neutrophil entry into the airways of Be-exposed mice would be attenuated by anti-TNF-α treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that AM cell death and DAMP release occur following single low-dose exposures to either beryllium sulfate (which forms beryllium hydroxide in airway fluids) or crystalline beryllium hydroxide (Be) particles (2). DNA and IL-1α released from Be-exposed AMs induce upregulation of CD80 on cDCs via the MyD88-dependent receptors TLR9 and IL-1R1 (2,12,36). In addition, DNA released by Be-exposed AMs promotes accelerated migration of cDCs from the lung to the LDLNs via TLR9 (2).…”
Section: Introductionmentioning
confidence: 99%